2005
DOI: 10.2108/zsj.22.1353
|View full text |Cite
|
Sign up to set email alerts
|

Potamothrix scleropenis sp. nov. (Oligochaeta: Tubificidae) from Fuxian Lake, the Deepest Lake in Southwest China

Abstract: -Potamothrix scleropenis sp. nov. (Tubificidae: Tubificinae) is described from the profundal zone (74 m) of Fuxian Lake, the deepest lake (up to 155 m) on the Yunnan-Guizhou Plateau in China. The new species is assigned to Potamothrix because of its short vasa deferentia and its tubular atria without ejaculatory ducts and prostate glands. It differs from congeners by its cuticularized penis sheaths; bifurcated, strongly curved spermathecal chaetae; bifurcated lower prongs of bifids; and feathered hairs. P. scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…The latter was transferred into the genus Haber, with some hesitation, already by Holmquist (1979) and, decisively, by Milligan (1986. Cui & Wang (2005, 2012a also discovered a separate, apparently monophyletic species group of this genus in ancient lakes of the Yunnan Plateau, southern China ( Fig. 2, 3).…”
Section: History Of the Genusmentioning
confidence: 92%
“…The latter was transferred into the genus Haber, with some hesitation, already by Holmquist (1979) and, decisively, by Milligan (1986. Cui & Wang (2005, 2012a also discovered a separate, apparently monophyletic species group of this genus in ancient lakes of the Yunnan Plateau, southern China ( Fig. 2, 3).…”
Section: History Of the Genusmentioning
confidence: 92%
“…Among oligochaete species, Potamothrix scleropenis is endemic (Cui and Wang, 2005), and the specific identities of another six, Potamothrix sp.1, Potamothrix sp.2, Potamothrix sp.3, Tubificinae gen. sp.1, Tubificinae gen. sp.2, and Tubificinae (?) gen.…”
Section: Article In Pressmentioning
confidence: 99%
“…The results, including community structure, characteristics of the macrofauna, seasonal changes and environmental parameters, are dealt with in the present paper. A new endemic species found during the work was described previously (Cui and Wang, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…During a limnological investigation of lakes in this province in 2002-2003, a number of oligochaete samples were collected. In five previous accounts (Cui and Wang 2005, 2008, 2009, 2012; Cui et al 2008), 31 species representing 14 genera were reported on the basis of the collected material. As a serial study, this paper gives the description of three new species of Potamothrix Vejdovský & Mrázek, 1902 (Oligochaeta: Naididae, Tubificinae) from Fuxian Lake, Potamothrix praeprostatus sp.…”
Section: Introductionmentioning
confidence: 99%